Research of Multi-layer DEM Modeling and Its Application in Stratum Visualizatio - WEI Yong-yong (Gong-kuang zidonghua, 2011)
The paper proposed a method of using visual language IDL as modeling tool to realize 3D visualization of stratum. Basic idea of the method is as following: (1) Obtaining statue data of stratum, making interpolation analysis of the data, and expressing surface of stratum by regular or irregular grid networks to form single-layer DEM. (2) Interpolating or fitting each surface of stratum according to forming method of single-layer DEM so as to obtain distribution of 3D space of different stratum. If there is no fault in stratum, connecting the grid networks of adjacent surfaces of stratum to build topological relation, which can obtain solid model of stratum. If there is intersection in stratums, doing detection of sample points or height judgment for cross region to determine range of the cross region to build 3D model of stratum. (3) Constructing volume data, using multi-layer DEM to make hierarchical assignment, and using different properties to mark stratums, which can realize visualization of geological space. The test result showed that the method has certain practicality.